Formulasi dan Uji Stabilitas Krim Ekstrak Aseton Biji Alpukat - Suradnyana, I Gede Made; Mendra, Ni Nyoman Yudianti; Juliadi, Debby; Suena, Ni Made Dharma Shantini (Jurnal Ilmiah Medicamento, 2024)
UV radiation can cause skin damage, thus requiring sunscreen and antioxidants for protection. Sunscreen absorbs or reflects UV rays, while antioxidants help increase antioxidant levels in skin tissues. Avocado seeds have potential as sunscreen and antioxidant agents, as the seed extract contains catechin, which can inhibit the enzymes tyrosinase, elastase, hyaluronidase, and collagenase. This study aims to determine the physical and chemical stability and the sunscreen and antioxidant activity of acetone avocado seed extract cream. The research stages included phytochemical screening, determination of total flavonoid content, antioxidant activity of the extract, cream formulation, physical and chemical stability tests, and sunscreen and antioxidant activity stability tests. The results showed that the extract tested positive for flavonoids, tannins, triterpenoids, phenols, and saponins. The extract's total flavonoid content and IC50 were 68.58±0.88 mg QE/100 g and 7.14 µg/ml, respectively. After six months of storage, there were changes in the color and spreadability of the cream. The spreadability significantly decreased from 50.87±3.17 to 35.21±2.09 g.cm/second, the total flavonoid content decreased from 9.16±0.27 to 4.48±0.16 mg QE/100 g, and the antioxidant activity significantly decreased from 7.41 to 18.72 µg/ml. Additionally, there was a significant increase in the SPF value from 1.62±0.01 to 1.87±0.06. Based on these results, the acetone avocado seed extract cream was unstable regarding physical, chemical, sunscreen, and antioxidant activity after six months of storage at room temperature. To improve the stability of the preparation, buffering in an acidic environment, adding antioxidants such as ascorbic acid, and storing at a cool temperature, are recommended.